Allocations of Sunk Capacity Costs and Joint Costs in a Linear Principal-Agent Model. - Hemmer, Thomas (The Accounting Review, 1996)
Examines the allocation of sunk capacity costs and joint costs. Trade-off between risk-sharing and incentives; Optimal capacity cost allocation as a function of budgeted volume; Previous research on capacity cost allocation; Insights from principal-agent theory.